Human behavior in household energy use and the implications of energy efficiency delivery: a case of Nigeria - Abdul Majid, Noor Hanita; Hussaini, Ibrahim Udale (2012)
Although the term energy efficiency is technologically focused it has a behavioral content due to the associated energy conservation practice involved. The technology aspect applies essentially to the application of new or better technology in order to derive some output or level of service for less input energy, while the conservation aspect is attributed to behavior (NEB, 2009). In an attempt to underscore this postulation social survey of some households in Bauchi town, Nigeria is undertaken. The principal objective is to determine the influence of human behavior in energy efficiency delivery in the households. The result reveals a much low level of energy efficiency practice by the occupants due largely to lack of awareness and requisite knowledge on the phenomenon of energy efficiency. Finally, the study highlights on the implications of good energy efficiency practice in household energy use as derived from the present as well as past studies in a bid to attain energy efficiency.